Standards in semen examination: publishing reproducible and reliable data based on high-quality methodology. Issue 11 (16th September 2022) - Björndahl, Lars; Barratt, Christopher L R; Mortimer, David; Agarwal, Ashok; Aitken, Robert J; Alvarez, Juan G; Aneck-Hahn, Natalie; Arver, Stefan; Baldi, Elisabetta; Bassas, Lluís; Boitrelle, Florence; Bornman, Riana; et al.
Abstract: Biomedical science is rapidly developing in terms of more transparency, openness and reproducibility of scientific publications. This is even more important for all studies that are based on results from basic semen examination. Recently two concordant documents have been published: the 6th edition of the WHO Laboratory Manual for the Examination and Processing of Human Semen, and the International Standard ISO 23162:2021. With these tools, we propose that authors should be instructed to follow these laboratory methods in order to publish studies in peer-reviewed journals, preferable by using a checklist as suggested in an Appendix to this article.